PENGEMBANGAN MEDIA PEMBELAJARAN GEOBOARD UNTUK KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SEKOLAH DASAR - Kris Aflia; Yuyu Yuhana; Trian Alamsyah (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aimed to determine the worthiness of Geoboard media and to identify the students' mathematical understanding ability after the implementation of Geoboard media in learning mathematics at grade IV SDN Serang 11. Geoboard media is a tool for teaching mathematics at elementary schools to embed the concepts/geometry, such as introducing plane figures, instilling the understanding about the concept of plane figures, and determining the area and perimeter. The method of this research was Research and Development (R&D) with the stages of problem analysis, data collection, product design, design validation, design revision, and limited product trials. Based on the results of the study, it can be concluded that Geoboard Media which was designed like a chessboard was developed based on the validation results with the score reaching 90% from material experts, 88% from media experts, and 93,5% from students’ responses. These results were categorized as Very Appropriate. Using Geoboard media for learning plane figures was considered to be effective to enhance students' mathematical understanding as it was obtaining that the average score was above the KKM (81.75%). After conducting several stages of validation, the final product of Geoboard learning media was considered to be very suitable, efficient, and attractive to be used as a learning media for mathematics learning, especially for plane figures materials, at grade IV SDN Serang 11.